Evaluation of Procalcitonin Levels in Patients with Various Forms of Acute Coronary Syndrome, Depending on the Presence of Adverse Hospital Outcomes - O. M. Drapkina; V. A. Zakharova (Столичная издательская компания, 2021)
Aim. to study the levels of procalcitonin in patients with various forms of acute coronary syndrome (ACS), depending on the presence of adverse hospital outcomes.Materials and Methods. The study included 222 patients admitted to the emergency cardiology department with a diagnosis of ACS in the period from March 2014. until January 2017. Of these, 106 (47.7 %) patients were diagnosed with unstable angina (NS) and 116 (52.3%) with myocardial infarction (MI). Non ST segment elevation MI (NSTEMI) was diagnosed in 47 (40.5%) patients with MI, and ST elevation MI (STEMI) - in 69 (59.5%) patients with MI. After the assessment of the patient's compliance with the criteria for inclusion/exclusion in the study, the procedure for signing the patient's informed consent form was carried out. The protocol of the study was approved by the local Ethics committee of the M. E. Zhadkevich State Clinical Hospital. In each study subgroup, the presence of adverse outcomes during the current hospitalization was assessed: cardiovascular death, nonfatal MI, nonfatal acute cerebrovascular accident, acute heart failure, as well as a combined endpoint, including all of the listed adverse outcomes. All patients, in addition to routine laboratory methods of investigation, were examined for the level of procalcitonin at admission to the hospital, on 2-3 and 4-5 days.Results. Patients with MI compared to patients with NS were characterized by a large number of registered endpoints in general (24.1% vs. 6.6%, p<0.001), while in the group of patients with MI, cardiovascular death was more often recorded (10.3% vs. 0.9%, p<0.001) and acute heart failure (12.9% vs. 5.6%, p=0.009). Patients with MI, in particular with STEMI, who had adverse hospital outcomes, were characterized by statistically significantly higher levels of procalcitonin compared to patients without adverse hospital outcomes. Patients with STEMI showed significantly higher levels of procalcitonin at all stages of the disease, and patients with MI-only at 2-3 and 4-5 days. There were no statistically significant differences in the level of procalcitonin at all stages of the disease in patients with NSTEMI and with unstable angina, depending on the hospital outcomes.Conclusion. Elevated procalcitonin levels in patients with MI, in particular with STEMI, are associated with adverse hospital outcomes; for other forms of ACS, no statistically significant differences were observed with different hospital outcomes.